2008
DOI: 10.1021/jp8031176
|View full text |Cite
|
Sign up to set email alerts
|

Short Hydrogen Bonds at the Water/TiO2 (Anatase) Interface

Abstract: The nature of peculiar, short H bonds formed by water molecules in contact with the (101) anatase surface and their effects on the structural and vibrational properties of the first water layers adsorbed on the same surface have been investigated by performing density functional theory (DFT) total energy calculations and ab initio molecular dynamics (AIMD) simulations at different temperatures. Present results show that these short H bonds originate from a water/anatase interface effect related to an electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 28 publications
8
72
0
Order By: Relevance
“…They observed that this reaction occurred at more negative potentials for A TiO 2 (001). This was linked to a more negative flatband potential for A TiO 2 (001) (by 0.06 V) that the authors attributed to a greater ability of this surface to thermally dissociate water in comparison with the A TiO 2 (101) surface [1681][1682][1683][1684]. As mentioned above, the (001) surface is a rough-and-trough reconstructed structure possessing (4×1)/(1×4) order.…”
Section: Anatase Surfacesmentioning
confidence: 91%
See 1 more Smart Citation
“…They observed that this reaction occurred at more negative potentials for A TiO 2 (001). This was linked to a more negative flatband potential for A TiO 2 (001) (by 0.06 V) that the authors attributed to a greater ability of this surface to thermally dissociate water in comparison with the A TiO 2 (101) surface [1681][1682][1683][1684]. As mentioned above, the (001) surface is a rough-and-trough reconstructed structure possessing (4×1)/(1×4) order.…”
Section: Anatase Surfacesmentioning
confidence: 91%
“…Fundamental studies of the chemistry of water (and hydroxyls) on single crystal TiO 2 surfaces provide a starting point for understanding the photochemical properties of this process [853]. Extensive experimental [138,192,194,195,199,527,566,580,792,795,797,799,803,804,807,810,843,852,1681,1683,[1712][1713][1714][1715][1716][1717] and theoretical [193,522,527,792,810,824,826,830,831,1660,1682,1684,1711,1712,[1717][1718][1719] work has been invested in understanding the molecular-level interactions of water with single crystal TiO 2 surfaces. This author is unaware of any reports to date in which photochemical water splitting (in either half reaction) was performed on a single crystal TiO 2 surface under UHV conditions.…”
Section: Water Splittingmentioning
confidence: 99%
“…), and protects them against movement, see Figure 4b. 16,[29][30][31][32][33] The attractive potential between the sulfonated monolayers and TiO 2 nanoparticles by van der Waals forces, which could be predicted using the Derjaguin, Landau, Verwey, and Overbeek (DLVO) theory, also promoted this interaction process. 26,27 As a consequence the formed NPs were firmly mixed and combined together with PEs in assist of these potential interaction.…”
Section: Tio2 Deposition and Reinforcement Mechanismmentioning
confidence: 99%
“…For instance, Inelastic Neutron Scattering (INS) measurements have led to vibrational spectra of adsorbed water on anatase powder and rutile rods [6,7]; this led to insight that confined adsorbed water molecules have dynamical and vibrational behaviour more redolent of less mobile ice vis-à-vis to a liquid [6,7]. This adsorbed-water vibrational behaviour has been studied in detail via molecular dynamics (MD) at interfaces of anatase-(101) and rutile-(110) with water [8,9]. Further, ab initio MD (AIMD) has led to important results in interesting studies recently [9,10] on librational and higher-frequency adsorbed-water modes.…”
Section: Introductionmentioning
confidence: 99%